Assessing Parent Perceptions of School Fit: The Development and Measurement Qualities of a Survey Scale. Issue 2 (2nd April 2016) - Bahena, Sofía; Schueler, Beth E.; McIntyre, Joseph; Gehlbach, Hunter
Abstract : Students whose school environment fits their developmental needs also typically experience academic success and increased motivation. Most investigations of school fit, which focus on teachers' and students' perceptions, have found a general decline in fit across the transition from elementary to middle school. However, little research has examined the school-child fit from the parent perspective. In this article, we first detail the development process behind a new survey measure of parent perceptions of school fit. Second, using three online panel-based samples of parents from across the country ( n 1  = 323, n 2  = 188, n 3  = 1, 033), we evaluate the scale's measurement properties and conduct exploratory analyses examining grade-level and income-based differences on reported school fit. Finally, in line with previous research, we find that parents of middle school children perceived statistically significantly worse fit than parents of elementary school children. Among parents of high school students, we found that, on average, high-income parents perceive statistically significantly better fit than low-income parents.